Leveraging Information Technology for Enhanced Information Quality and Managerial Performance - Sudarno; Novita Yulia Putri; Nicholas Renaldo; Marice Br. Hutahuruk; Cecilia (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
This study aims to analyze and understand the contribution of information technology and its impact on information quality and management performance in the digital printing industry. The approach used in this study is causality between variables, while the sampling technique used is a census method, which means that the entire population is a target sample of 52 respondents who are business leaders. To measure the variables in this study, variable indicators consisting of a five-level Likert scale have been used, while the analysis method used to demonstrate the hypothesis is SmartPLS Software. The results of this study find that information technology has a positive contribution to improving information quality and management performance in the digital printing industry. The results show that improving information quality and management performance can be achieved by using new information technology and computer-based telecommunications. It was also found that the quality of information has a positive and significant effect on improving managerial performance. This implies that to improve the management performance of the digital printing industry, information quality support is required so that the decisions taken are effective and relevant to achieving management performance and maintaining business continuity.